Characterization of gallium nitride materials for high-frequency and high-power devices - Yusuf Anindita Wibawa. (2009)
In recent years, a significant progress has been made in the development of III-V Nitrides based devices. Materials such as Aluminium Nitride, Gallium Nitride, Indium Nitride and their alloys have been attractive due to the wide band-gap characteristic.